Mobile learning and computational thinking - Freixo Nunes, José (2020)
Computational thinking can be thought of as an approach to problem solving which has been applied to different areas of learning and which has become an important field of investigation in the area of educational research. Its main conceptual tools are decomposition, pattern recognition, abstraction and algorithm design. In the project described here, this new paradigm was used with ninth grade pupils who were involved in the development of mobile applications (apps). The choice of m-learning is motivated by its many affordances for changing or adding value to learning and teaching processes. One of these is that with mobiles it is possible to carry out new types of distributed learning activities that are not strictly confined to the classroom. To support our pupils in app development, we used the conceptual tools of computational thinking and the App Inventor platform developed at MIT. We explained how software development can be made easier and more understandable without resorting to long and complex coding activities. For instance, in 1981 IBM launched the personal computer, IBM PC (Freed & Ishida, 1995) and users were able to develop their own programs using a BASIC programming language interpreter (Beginner’s All-purpose Symbolic Instruction Code) and a manual with detailed explanations on how to program, both included in the computer.